Reviewing Information and Electronic Transaction Act from a Convention on Cybercrime of 2001 - Wahyu Priyanka Nata Permana (Universitas Ahmad Dahlan, 2021)
Introduction to the Problem: This research analyses the norms of substantive criminal Law regarding Information and Electronic Transaction Act Number No. 11 of 2008 in conjunction with Bill Number 19 of 2016 on Amendments to Information and Electronic Transactions Act No. 11 of 2008 and its compliance with the Convention on Cybercrime, 2001.Purpose/Objective Study: This research aims to analyze the conformity of offenses, criminal liability, and criminal sanction in the Information and Electronic Transaction Act (IETA) to the principles promulgated in the Convention on Cybercrime, 2001.Design/Methodology/Approach: This research is a normative legal study using statute and conceptual approaches.Findings: This study concluded that, in general, offenses regulated in IETA had confirmed the Convention. Nevertheless, the provision of computer-related fraud in IETA has a broader range than that of the Convention. IETA also lacks formulation concerning when and who bears criminal liability for corporate crime as suggested in the Convention. The research also finds that IETA did not adopt the principle of effectiveness and proportionality in promulgating both punishment and treatment. This study suggests that IETA should adopt criminal liability for a corporation, set the penal punishment proportionate to the seriousness of conduct and culpability of the actor, and regulate treatment.Paper Type: Research Article